Kategoria duchowości we współczesnej psychologii - Chojniak, Arleta (Poznańskie Studia Teologiczne, 2011)
Nowadays it is noted that some traditional psychological categories are inadequate to explain the specificity of human activity. For example the concept of personality seems to be insufficient to express how people function. Spirituality is one of the categories which could describe the form of a person’s inner experience determined by cultural meanings and values. The main aim of this paper is to consider some new psychological conceptions that include the spiritual dimension of a human. The author analyzes three approaches. The first one, proposed by Anna Galdowa, emphasizes spiritual development. The project of Irena Heszen focuses on the connection between spirituality and psychosomatic health. The third conception, developed by Zohar and Marshall, considers spiritual intelligence and indicates the neurological substrate of spirituality Keywords